A transparência pública na Convenção de Mérida como instrumento de prevenção à corrupção nas licitações fiscalizadas pelo TCE/PB - Almeida, Laryssa Mayara Alves de (2018)
United Nations Convention against Corruption (UNCAC) was ratified by Brazil in 2006 (Decree 5687/2006), as the only international treaty that establishes transparency as a principle and preventive measure against corruption in public bids. If the world-wide movement of corruption networks does not obey borders, then the fight against corruption must also cross the walls of local institutions in building wider networks. It is with this objective that the public sector transparency parameter established in the UNCAC is observed, and the application of the same in the monitoring of the bidding processes carried out by the Court of Audit of the State of Paraiba (TCE/PB) is analyzed. Thus, the research questions how the application of the public sector transparency parameter established in the UNCAC contributes to the application of preventive policies and practices by the TCE/PB, facing the cultural and institutional challenges of corruption in the public bids. The research is organized in the field of International Law and Administrative Law, with the scope of investigating how the international measures for the prevention of corruption are in line with the actions of external control in relation to the supervision of public bids in the Brazilian State of Paraiba and in its Municipalities. The methodology chosen for this work consists of an deductive approach, bibliographical research for the construction of the theoretical framework and documentary analysis, having as source of data, the reports of the activities of the TCE/PB published between 2006 and 2017 and its normative acts referring to the public bids. To identify possible deficiencies of the current institutional design of the TCE/PB and propose possible normative and practical improvements. The results indicate the urgency of increasing the transparency of information in published documents, creating spaces for society's participation and adopting continuous training programs for TCE-PB employees on trends, problems and needs experienced in the fight against corruption.